Quantification of human error rate in underground coal mines - A fuzzy mapping and rough set based approach - Gupta S.; Kumar P.; Karmakar N.C.; Palei S.K. (My University, 2025)
A precise value of human error rate is imperative to probabilistic safety and risk analysis. Prevailing methods for error quantification are domain specific and provide a crude estimate only. Human error rate (HER) in mines are influenced by the context or performance conditions that are assessed using a set of context describing factors (CDFs). A set of linguistic levels describe the state of the CDFs. An exhaustive set of possible combination of CDFs represent the universal set of context. The relation between context and human error rate can be modeled by mapping the fuzzy set of context to the fuzzy set of HER. The HER of a mine can be estimated from the subjective assessment of CDFs using the concept of rough set. © 2013 IEEE.